PROTACs: Mechanism and Bioavailability enhancement strategies by nanotechnology, RNA viral infections (vaccine strategy) and Prodrug development - Sanaul Mustafa; Md Sabir Hussain Siddiquee (German Journal of Pharmaceuticals and Biomaterials)
Proteolysis Targeting Chimera (PROTACs) are a brand-new concept of therapeutics that use the ubiquitin-proteasome system for selective degradation of disease-related proteins. Like other therapeutics, PROTACs function by recruiting a protein target and a ubiquitin ligase that leads to the degradation of the target protein; however, unlike most other drugs, PROTACs do not simply disable the target’s function through steric hindrance. As a result of this present review, the application of PROTACs will be discussed in oncology, leukemia, and neurodegenerative diseases. However, there are considerable difficulties regarding the bioavailability of PROTACs; one of which is selecting the appropriate degron. This review describes the issues of bioavailability that are related with PROTACs, such as solubility and stability issues, and proposed tactical decisions, which could be used under those conditions. The newest approaches in nanotechnology-aided drug delivery and the use of nanocarriers to address the limitations in PROTACs and their pharmacokinetic and pharmacodynamic properties are discussed. They improve the solubility and stability of PROTACs, allow for targeted delivery to the tumour site and minimize toxicity to healthy cells. Moreover, arguably the most interesting virtue of PROTACs is its applicability for RNA viral infections (new vaccine design) based on the degradation of viral proteins. An idea for the field of antiviral therapy, this invention defines a new horizon for the management of diseases that have not responded to traditional methods. In addition, the review focuses on the advanced techniques on the application of prodrug strategies in PROTACs. These inactive PROTACs are then converted to prodrugs to enhance their uptake into target tissues thereby increasing the concentrations at the target site and at the same time minimizing on the adverse effects that may be caused by higher concentrations in the entire body. Also, when PROTACs are incorporated into sophisticated drug delivery systems, their desirability and selectivity are further improved beyond existing issues related to small-molecule inhibitors. This review also includes new progress, clinical applicability, and development trend of PROTAC for the change of disease therapy and drug delivery.